Hair sterol signatures coupled to multivariate data analysis reveal an increased 7 beta-hydroxycholesterol production in cognitive impairment - Son, Hyun-Hwa; Lee, Do-Yup; Seo, Hong Seog; Jeong, Jihyeon; Moon, Ju-Yeon; Lee, Jung-Eun; Chung, Bong Chul; Kim, Eosu; Choi, Man Ho (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Altered cholesterol metabolism could be associated with cognitive impairment. The quantitative profiling of 19 hair sterols was developed using gas chromatography-mass spectrometry coupled to multivariate data analysis. The limit of quantification of all sterols ranged from 5 to 20 ng/g, while the calibration linearity was higher than 0.98. The precision (% CV) and accuracy (% bias) ranged from 3.2% to 9.8% and from 83.2% to 119.4%, respectively. Among the sterols examined, 8 were quantitatively detected from two strands of 3-cm-long scalp hair samples of female participants, including mild cognitive impairment (MCI, n = 15), Alzheimer's disease (AD, n = 31), and healthy controls (HC, n = 36). The cognitive impairment (MCI or AD) was correlated with a higher metabolic rate than that of HCs based on 7 beta-hydroxycholesterol (P<0.005). Significant negative correlations (r = -0.822) were detected between Mini-Mental State Examination (MMSE) scores and hair sample metabolic ratios of 7 beta-hydroxycholesterol to cholesterol, which is an accepted, sensitive, and specific tool for discriminating HCs from individuals with MCI or AD. In conclusion, improved diagnostic values can be obtained using hair sterol signatures coupled with MMSE scores. This method may prove useful for predictive diagnosis in population screening of cognitive impairment. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: ALZHEIMERS ASSOCIATION WORKGROUPS; CHOLESTEROL HOMEOSTASIS; DIAGNOSTIC GUIDELINES; CEREBROSPINAL-FLUID; NATIONAL INSTITUTE; CHRONIC STRESS; DISEASE; CORTISOL; MARKER; BRAIN